Resolution of Land Disputes Through Mediation - Siti Rahmah; Kadir, M. Yakub Aiyub; Megawati, Cut; Astini, Dewi; Sulfi, Aina (Universitas Sumatera Utara, 2024)
This study delves into mediation as a means of dispute resolution, particularly outside the courtroom, contrasting with the prevalent use of courts, especially in land dispute cases. It highlights mediation as a direct process with enduring positive effects, aiming to achieve peace and mutually beneficial solutions while ensuring no party is harmed. The resulting agreement from mediation holds legal weight and is considered final, bolstered by a peace agreement signed between the involved parties and the mediator. The study aims to evaluate the efficacy of mediation as a conflict resolution tool outside the courtroom, culminating in a documented agreement. Employing normative legal research methods with a statutory approach, the study meticulously examines all relevant laws and regulations. Data collection utilizes literature review methods, providing a comprehensive reference base to support research on the role of mediators in dispute resolution. The gathered information is systematically compiled and analyzed using descriptive methods. In conclusion, mediation has demonstrated its effectiveness as an alternative to court proceedings in settling disputes. The mediator, acting as a facilitator, helps the parties reach an agreement. The outcomes of mediation, documented in the peace agreement, are registered in court, providing legal validity and conclusiveness to the agreed-upon terms.